Vocabulary learning strategies used by non-English major students: A case study at Saigon University - Nguyen Quang,; Nguyen Quang, Minh Triet (Technium Social Sciences Journal, 2025)
This study investigated the vocabulary learning strategies employed by 59 sophomore students majoring in Culture and Tourism at Saigon university. Participants were selected through convenience sampling from among sophomore students majoring in Culture and Tourism at a university in Saigon. They had completed a Basic English course and were currently enrolled in English for Specific Purposes. Recognizing the crucial role of vocabulary in language learning and the need for effective learning strategies, this research aimed to identify the most and least frequently used strategies by these non-English majors. Furthermore, the study explored the underlying reasons for the frequent use of specific strategies. The findings of this study are expected to provide valuable insights into the vocabulary learning behaviors of this specific student population and offer practical guidance for enhancing their language learning experience.